2021
DOI: 10.1002/casp.2525
|View full text |Cite
|
Sign up to set email alerts
|

Youth's experiences with inclusion, isolation, and discrimination in the LGBTQ+ community

Abstract: It has been well established that sexual‐ and gender‐minority youth are vulnerable to judgement and maltreatment by non‐LGBTQ+ peers. However, little research has focused on the experiences and interactions among youth specifically within the LGBTQ+ community. The purpose of the present study was to examine inclusion, isolation and discrimination within the LGBTQ+ community, while considering youths' sense of identity. Participants were 122 sexual minority and gender diverse youth between the ages of 14 and 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…This finding was especially salient for LGBTQ+ participants. This is consistent with literature indicating associations between being strongly identified as LGBTQ+ and LGBTQ+ community involvement (Closson & Comeau, 2021; Frost & Meyer, 2012), and literature about “second-gen” queer youth (Kuvalanka & Goldberg, 2009). Interestingly, participants with divorced caregivers appeared likely to emphasize local community involvement, perhaps because support outside of the family can be heavily impactful for youth with divorced caregivers (A.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding was especially salient for LGBTQ+ participants. This is consistent with literature indicating associations between being strongly identified as LGBTQ+ and LGBTQ+ community involvement (Closson & Comeau, 2021; Frost & Meyer, 2012), and literature about “second-gen” queer youth (Kuvalanka & Goldberg, 2009). Interestingly, participants with divorced caregivers appeared likely to emphasize local community involvement, perhaps because support outside of the family can be heavily impactful for youth with divorced caregivers (A.…”
Section: Discussionsupporting
confidence: 91%
“…Participants with these identities spoke about such exclusionary messages; gatekeeping made them feel unwelcome in the community. These experiences reflect stereotypes perpetuated in society, including within the LGBTQ+ community (Closson & Comeau, 2021; Levitt et al, 2023; McCormick & Barthelemy, 2021). Further, they point to a need for greater societal understanding of gender and sexuality.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies showed that, among LGBTQIA+ identities, the members more at risk of being negatively evaluated by others are those who disconfirm normative expectations concerning binary sexuality (Matsick & Rubin, 2018) and gender (Salvati et al, 2018). Moreover, a recent study showed that gender minorities might be discriminated against and less included because of the cisnormative narrative that permeates the LGBTQIA+ communities (Closson & Comeau, 2021). Little research has explicitly focused on attitudes and representations of nonbinary gender identities inside and outside the LGBTQIA+ population.…”
Section: Discussionmentioning
confidence: 99%